2021
DOI: 10.1002/agt2.60
|View full text |Cite
|
Sign up to set email alerts
|

Stereodefined tetraarylethylenes: Synthesis and applications

Abstract: Luminescent materials with efficient aggregate‐state emissions are of growing interest due to their widespread applications in chemo‐/biosensing and optoelectronic devices. Aggregation‐induced emission (AIE) opens a new avenue for the applications of aggregate‐state luminescent materials. Among the AIE luminogens (AIEgens), tetraarylethylenes (TAEs) are typical AIEgens with a simple molecule scaffold and could be utilized as a framework for further elaboration, enabling structure‐property‐function relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 110 publications
0
9
0
Order By: Relevance
“…Although tetraarylethenes have gained significant attention for their characteristic properties such as aggregation induced emission, 5,6,52 installation of four different aryl groups on one ethene unit remains challenging and often requires lengthy steps. [8][9][10] Finally, transformations of oxaborole 2co-A were also performed (Fig. 5c).…”
Section: Fig 3│regioselectivity In Borofunctionalization Of Unsymmetr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Although tetraarylethenes have gained significant attention for their characteristic properties such as aggregation induced emission, 5,6,52 installation of four different aryl groups on one ethene unit remains challenging and often requires lengthy steps. [8][9][10] Finally, transformations of oxaborole 2co-A were also performed (Fig. 5c).…”
Section: Fig 3│regioselectivity In Borofunctionalization Of Unsymmetr...mentioning
confidence: 99%
“…Multisubstituted alkenes play a significant role in various fields such as pharmaceuticals, [1][2][3][4] and materials science [5][6][7] due to their diverse functional group arrangements. The stereo-and regioselective synthesis of multisubstituted alkenes is a crucial aspect of organic chemistry [8][9][10] as it allows the synthesis of specific isomers with distinct physical and chemical properties including bioactivities. 11 Hence, the development of efficient methods for the stereo-and regiocontrolled synthesis of multisubstituted alkenes is essential in modern organic chemistry, as existing methods such as the alkenation reactions of carbonyl compounds (including Wittig and Mukaiyama-McMurry reactions) and alkene metathesis usually result in only moderate stereoselectivity (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Under this guidance, many RIR-type AIE units, such as tetraphenylethylene (TPE), tetraphenylbenzene (TPB) and tetraphenylpyrazine (TPP), have been reported and widely used in the development of multifunctional luminescent materials. [19][20][21][22][23][24] In contrast, RIV-type AIEgens are barely reported and used in practical applications because of their complicated synthetic procedures and high costs. [25][26][27] Recently, a new kind of RIV-type AIEgen, namely oxacalix [2] aromatic [2]pyrazine (OAP) has been reported by our group, and it can be used for the construction of luminescent metalorganic frameworks (MOFs) due to the built-in coordination sites of pyrazine units.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Since then, it has contributed a lot both in fundamental research and in practical applications. [3][4][5][6][7][8][9][10][11][12][13] Luminogens with AIE features (AIEgens), which exhibit faint luminescence in solution but give bright emission in the aggregate or solid states, usually have the merits of large Stokes shifts, high emission quantum yields and superior photostability. Studies indicated that the suppression of p-p interactions in molecular packing and restriction of intramolecular motions (RIMs) is the major mechanism of AIE.…”
Section: Introductionmentioning
confidence: 99%